Ask Question
12 April, 22:52

Given: F (x) = 3x2 + 1, G (x) = 2x - 3, H (x) = x

F (-2) =

+2
Answers (1)
  1. 13 April, 00:50
    0
    Use the given functions to set up and simplify:

    F (-2) and that equals to 13

    Step-by-step explanation:

    So, therefore, your answer to the problem is 13.
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Given: F (x) = 3x2 + 1, G (x) = 2x - 3, H (x) = x F (-2) = ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers